Comparison of myofibrillar protein degradation, antioxidant profile, fatty acids, metmyoglobin reducing activity, physicochemical properties and sensory attributes of gluteus medius and infraspinatus muscles in goats - Adeyemi, Kazeem Dauda; Shittu, Rafiat Morolayo; Sabow, Azad Behnan; Abubakar, Ahmed Abubakar; Karim, Roselina; Karsani, Saiful Anuar; Sazili, Awis Qurni (BioMed Central, 2016)
Background: The functionality of myofibrillar proteins is a major factor influencing the quality attributes of muscle foods. Nonetheless, the relationships between muscle type and oxidative changes in chevon during ageing are meagrely elucidated. Postmortem changes in antioxidant status and physicochemical properties of glycolytic gluteus medius (GM) and oxidative infraspinatus (IS) muscles in goats were compared. Methods: Twenty Boer bucks (9–10 months old, body weight of 36.9 ± 0.725 kg) were slaughtered and the carcasses were subjected to chill storage (4 ± 0.5 °C). Analyses were conducted on GM and IS muscles sampled on 0, 1, 4 and 7 d postmortem. Results: Chill storage did not affect the antioxidant enzyme activities in both muscles. The IS had greater (P < 0.05) superoxide dismutase and catalase activities than GM. Carotenoid and tocopherol contents did not differ between muscles but decreased (P < 0.05) over storage. The IS had higher (P < 0.05) glycogen and ultimate pH and lower (P < 0.05) shear force and cooking loss than GM. The carbonyl content, % metmyoglobin, drip loss and TBARS increased (P < 0.05) while free thiol, metmyoglobin reducing activity (MRA), shear force and myoglobin decreased (P < 0.05) over storage. Muscle type had no effect (P > 0.05) on free thiol, MRA and TBARS. The GM had lower (P < 0.05) redness on d 0 and 1 than IS while the IS had greater carbonyl, % metmyoglobin and drip loss than GM on d 7. The reflective density of slow myosin heavy chain (MHC) was higher (P < 0.05) while the density of fast MHC and actin was lower (P < 0.05) in IS than GM. Regardless of muscle type, the density of MHC decreased (P < 0.05) while that of actin was stable over storage. Nonetheless, the degradation of fast and slow MHC was greater (P < 0.05) in IS than GM. Muscle type had no effect (P > 0.05) on consumer preference for flavour, juiciness and overall acceptability. However, IS had higher (P < 0.05) tenderness score than GM on d 1 and 4 postmortem. Intramuscular fat was higher (P < 0.05) in IS compared with GM. Fatty acid composition did not differ between the muscles. However, GM had lower (P < 0.05) n-6/n-3 ratio than IS. The n-3 and n-6 PUFA declined (P < 0.05) while the SFA increased (P < 0.05) over storage. Conclusion: The changes in myofibrillar proteins and physicochemical properties of goat meat during postmortem chill storage are muscle-dependent.